Sex dimorphism in children and youths from large towns, small towas and rural areas - Jedlińska, Wanda; Waliszko, Anna (Anthropological Review, 1981)
The intensity of sex dimorphism and size of secular changes in it were studied in three differentiy urbanized environments, i. e. — large towns, small towns and rural areas. The analysis was based on the materials collected during two extensive anthropological surveys carried out in 1966 and 1978 and comprising children and youths aged 7 through 18. The set of 11 anthropometric features, most significant in body build assessments was involved; they were: body height, leg length, sitting height, biacromial diameter, biiliocristale diameter, knee width, body weight, chest circumference, waist circumference, hip circumference, subscapular skinfold thickness. It was found that the environmental differences in sex dimorphism are recently more pronounced than they were in 1966. In the both surveys the greatest. differences between sexes are observed in the large town materials and the smallest in the rural areas. The secular changes in sex dimorphism are also most intensive in the large town sample whereas they are similar in both other populations (slightly more pronounced in small towns). Secular changes in sex dimorphism are most intensive during the postpubertal phase. During the period 1966 - 1978 an intensification of intersex differences in the features under study was stated. This phenomenon results from an increase of differences in the , male” traits (those continuing to be bigger in boys throughout the all — or only with an exception for pubescence — developmental phases) as well as from a decrease in , female” traits (those continuously bigger in girls). Thus, the highest secular intensification of sex dimorphism occurs in chest and waist circumferences and in biacromial diameter; the most marked decrease is observed in skinfold thickness, hip circumference and biiliocristale diameter. It was also found that, due to the higher acceleration of growth of boys, girls outgrow boys during the puberal phase to the lesser degree in 1978 than it was found in 1966.